Tandem Mass Tag-Based Quantitative Proteomic Analysis Reveals Pathways Involved in Brain Injury Induced by Chest Exposure to Shock Waves - Tong, Changci; Cong, Peifang; Liu, Ying; Shi, Xiuyun; Shi, Lin; Mao, Shun; Zhao, Yan; Hou, Mingxiao; Liu, Yunen (Frontiers in Molecular Neuroscience, 2021)
Recurrent chest blast exposure can lead to brain inflammation, oxidative stress and mental disorders in soldiers. However, the mechanism that underlies brain injury caused indirectly by chest blast remains unclear. It is urgent to find additional reliable biomarkers to reveal the intimate details of the pathogenesis of this phenomenon. We used the term tandem mass tag (TMT) labeling combined with liquid chromatography tandem mass spectrometry (LC-MS/MS) to screen for differentially expressed proteins in rat brain at different times points after chest blast. Data are available via ProteomeXchange with identifier PXD025204. Gene Ontology, Kyoto Encyclopedia of Genes and Genomes, DAVID, and Cytoscape were used to analyze the proteomic profiles of blast-exposed rats. In addition, we used western blotting to verify protein levels. We identified 6,931 proteins, of which 255 were differentially expressed. Among these, 43, 84, 52, 97 and 49 proteins were identified in brain tissues at 12 h, 24 h, 48 h, 72 h, and 1 w after chest blast exposure, respectively. Gene Ontology, Kyoto Encyclopedia of Genes and Genomes, Clusters of Orthologous Groups of proteins, and STRING analyses, indicated that brain damage caused by chest blast exposure involved many important biological processes and signaling pathways, such as inflammation, cell adhesion, phagocytosis, neuronal and synaptic damage, oxidative stress and apoptosis. Moreover, western blotting confirmed that these differentially expressed proteins and the affected signaling pathways were associated with brain damage caused by chest blast exposure. This study has identified potential protein biomarkers of brain damage caused indirectly by chest blast and has identified new targets for the treatment of this condition..